2016
DOI: 10.1534/g3.115.025577
|View full text |Cite
|
Sign up to set email alerts
|

The E2F-DP1 Transcription Factor Complex Regulates Centriole Duplication inCaenorhabditis elegans

Abstract: Centrioles play critical roles in the organization of microtubule-based structures, from the mitotic spindle to cilia and flagella. In order to properly execute their various functions, centrioles are subjected to stringent copy number control. Central to this control mechanism is a precise duplication event that takes place during S phase of the cell cycle and involves the assembly of a single daughter centriole in association with each mother centriole . Recent studies have revealed that posttranslational co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 88 publications
(118 reference statements)
5
15
0
Order By: Relevance
“…Our data indicate that fzr-1(bs31) embryos possess increased SAS-5 levels (~1.5fold), relative to wild-type embryos, while the levels of SAS-6 and TBG-1 appear to be unaffected in fzr-1(bs31) mutants ( Figure 4C). Our observation in SAS-6 levels in fzr-1(bs31) mutants is consistent with previous work by Miller et al, 2016, showing no increase in SAS-6 levels by the mat-3(bs29)/APC8 mutation that inhibits the APC/C function. These results suggest that C. elegans utilizes a different mechanism to control SAS-6 levels, unlike Human SAS-6 that is regulated by the APC/C-mediated proteolysis (Strnad et al, 2007).…”
Section: Loss Of Fzr-1 Results In Elevated Sas-5 Levelssupporting
confidence: 93%
See 1 more Smart Citation
“…Our data indicate that fzr-1(bs31) embryos possess increased SAS-5 levels (~1.5fold), relative to wild-type embryos, while the levels of SAS-6 and TBG-1 appear to be unaffected in fzr-1(bs31) mutants ( Figure 4C). Our observation in SAS-6 levels in fzr-1(bs31) mutants is consistent with previous work by Miller et al, 2016, showing no increase in SAS-6 levels by the mat-3(bs29)/APC8 mutation that inhibits the APC/C function. These results suggest that C. elegans utilizes a different mechanism to control SAS-6 levels, unlike Human SAS-6 that is regulated by the APC/C-mediated proteolysis (Strnad et al, 2007).…”
Section: Loss Of Fzr-1 Results In Elevated Sas-5 Levelssupporting
confidence: 93%
“…Consistently, 5% of zyg-1(it25); mat-3(or180) double mutants produce viable progeny while 100% of zyg-1(it25) or mat-3(or180) single mutant progeny die at 24° (Table 1). In support of our results, the mat-3(bs29) allele has been reported as a genetic suppressor of zyg-1 (Miller et al, 2016). Furthermore, we observed that the emb-1 mutation suppresses the centrosome duplication phenotype of zyg-1(it25) mutants at the semi-restrictive temperature 22.5°.…”
Section: Fzr-1 Might Function As a Part Of The Apc/c Complex To Regulsupporting
confidence: 90%
“…Consistently, 5% of zyg-1 ( it25 ) ; mat-3 ( or180 ) double mutants produce viable progeny while 100% of zyg-1 ( it25 ) or mat-3 ( or180 ) single mutant progeny die at 24° ( Table 1 ). In support of our results, the mat-3 ( bs29 ) allele has been reported as a genetic suppressor of zyg-1 ( Miller et al 2016 ). This result also indicates that the zyg-1 ( it25 ) mutation partially restores embryonic viability of mat-3 ( or180 ) mutants, suggesting a mutual suppression between zyg-1 and mat-3 .…”
Section: Resultssupporting
confidence: 91%
“…The phosphatase PP2A influences the SAS-5-SAS-6 complex by inhibiting both ZYG-1 and SAS-5 degradation (Kitagawa et al 2011a;Song et al 2011), while the transcriptional regulator E2F/DP1 negatively regulates SAS-6 expression and positively regulates ZYG-1 and other centriole duplication factors. Reducing E2F/DP1 can rescue reduced ZYG-1 function through the resulting increased SAS-6 levels (Miller et al 2016). Finally, negative regulation of SAS-5 levels also is important for the control of centriole duplication.…”
Section: Limiting Centriole Duplication By Controlling the Levels Of mentioning
confidence: 99%